Internalization of Sharia Economic Values ​​in the Tiba'iyah Kubro Tradition: Education for Sakinah Family Financial Management - Munawir; Wiwit Mustafidah (Simfoni Ilmu Cindekia, 2025)
The phenomenon of illegal online loans and moneylenders in rural areas poses a real threat to family economic resilience. This community service program aimed to improve Islamic financial literacy and family financial management skills (family sakinah) among women congregants in Karangdoro Village, Tegalsari, Banyuwangi. The method employed was Asset-Based Community Development (ABCD), by internalizing Islamic economic values into the local tradition of Tiba’iyah Kubro. The activity was conducted on September 14, 2025, involving 350 participants from 12 study groups. The results demonstrated a significant increase in participants’ cognitive understanding, with the average score of Islamic financial literacy rising from 38% to 64%. The program recommends the digitalization of financial recording instruments and the establishment of a Sharia cooperative to ensure the sustainability of congregants’ economic independence. Sociologically, this initiative successfully strengthened the function of the Majelis Tiba’iyah Kubro from merely a ritual forum into a platform for collective economic empowerment through the initiation of a social fund (Qardhul Hasan).